Assessment of Toxic Heavy Metal Content in Children Toys - Suwal, Anjana; Prajapati, Meera; Shah, Ram Charitra (Khwopa Journal, 2023)
The children toys are the most favorable things for children to play. But these children toys are not safe from toxic chemicals too. There is presence of different toxic heavy metals such as mercury, lead, barium, chromium, zinc etc. The standard value for different heavy metals is set up by the government of Nepal that came into effective from July 15, 2017. The standard was set up for the 12 toxic heavy metals as cadmium, chromium, lead, mercury, zinc, antimony, arsenic, barium, bisphenol A, bromine, selenium and phthalates. The study was focused on the study of the compliance of toxic heavy metals in children toys with the national standard. For the study total 52 toys were collected from different places of Nepal: Bhaktapur, Kathmandu, Lalitpur, Chitwan, Janakpur and Nepalgunj from the local vendors to the supermarkets. The toys were generally made up of plastic, rubber, metal, foam etc. After the collection and sampling of the toys they were tested in the lab of Nepal Handicraft Association of Nepal Bureau of Standard and Metrology (NBSM) by the X-Ray Fluorescence (XRF) technology. Among the 52 toys, no any heavy metals were detected in 15 toys and 37 toys were detected with multiple toxic heavy metals. The heavy metals detected in the toys were lead, cadmium, bromine, chromium, zinc and barium. Even most of the detected result is under the compliance it is very serious issue that the non-compliance result of heavy metals like lead is very much more (4688 ppm) than the standard value (90 ppm) in the toy: tortoise. In the same way, 22 children toys have the labelling and rest do not have the labelling. But the labelled children toys don’t have the labelling about the chemical safety. Though the national standard has been formulated the local or the parents themselves are unaware about the toxic heavy metals present in the toys. As well there has raised a big confusion in the standard of the toxic heavy metals as the new standard has been published omitting the standard of the heavy metals as phthalates, BPA, bromine and zinc. Thus, these points should be considered in order to implement the standard effectively and to save the children from the chemical hazards.